2014
DOI: 10.4161/rna.29440
|View full text |Cite
|
Sign up to set email alerts
|

RNase J is required for processing of a small number of RNAs inRhodobacter sphaeroides

Abstract: All bacteria contain multiple exoribonucleases to ensure a fast breakdown of different RNA molecules, either for maturation or for complete degradation to the level of mononucleotides. This efficient RNA degradation plays pivotal roles in the post-transcriptional gene regulation, in RNA processing and maturation as well as in RNA quality control mechanisms and global adaption to stress conditions. Besides different 3′-to-5′ exoribonucleases mostly with overlapping functions in vivo many bacteria additionally p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…In addition to RNase E, endoribonuclease G, which has strong homology to the N-terminal part of RNase E, and the double-strand–specific RNase III participate in endonucleolytic cleavage of RNA in Gram-negative bacteria ( Evguenieva-Hackenberg & Klug, 2009 ). R. sphaeroides also harbors an RNase J enzyme ( Rische-Grahl et al, 2014 ), which was shown to exhibit endonucleolytic activity in B. subtilis ( Even et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to RNase E, endoribonuclease G, which has strong homology to the N-terminal part of RNase E, and the double-strand–specific RNase III participate in endonucleolytic cleavage of RNA in Gram-negative bacteria ( Evguenieva-Hackenberg & Klug, 2009 ). R. sphaeroides also harbors an RNase J enzyme ( Rische-Grahl et al, 2014 ), which was shown to exhibit endonucleolytic activity in B. subtilis ( Even et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…The indirect effects of CrhR truncation on RNA turnover could be associated with the observed up-regulation of RNase J (slr0551). Although not studied in cyanobacteria, RNase J is known to perform functions in all aspects of RNA metabolism in a range of organisms [53][54][55]. Moreover, yeast two-hybrid screens indicated that the DEAD-box RNA helicase HP4 interacted with the RNase J homolog in C. reinhardtii [53].…”
Section: Altered Mrna Expression Correlates With Altered Cellular Mormentioning
confidence: 99%
“…To get more insight into the interplay of RNase E, RNase III and PNPase we analyzed the correlation of 3′ ends from the wild type, the pnp mutant, an RNase III mutant and a strain with reduced RNase E activity. In the RNase III mutant strain, the rnc gene was removed by homologous recombination [24]. Since RNase E is an essential enzyme in Rhodobacter sphaeroides, the rne mutant strain was achieved by replacing the native rne by the gene of the thermosensitive RNase E from E. coli [54].…”
Section: Intersection Analysismentioning
confidence: 99%
“…These are the RNase R, RNase D and RNase PH which catalyze mainly tRNA and rRNA processing reactions and all act in 3′-to-5′ direction [ 21 23 ]. In addition, RNase J1 is responsible for the maturation of the 23S rRNA and very few other transcripts [ 24 , 25 ]. In contrast to the other RNases, it processes RNA molecules in 5′-to-3′ end direction [ 26 ].…”
Section: Introductionmentioning
confidence: 99%